Virulence, structure, and triadimefon sensitivity of the Puccinia striiformis f. sp. tritici population in Shaanxi Province, China - Zhou, Aihong (Plant disease, 2024)
Stripe rust, caused by Puccinia striiformis f. sp. tritici (Pst), is the most destructive fungal disease affecting wheat in China, especially in Shaanxi Province, an important epidemiological region connecting the western Pst over-summer regions and the central and eastern spring epidemic regions in the country. In the present study, 291 Pst isolates from Shaanxi Province were studied for their virulence using two sets of wheat differentials, population structure using single-nucleotide polymorphism (SNP) markers, and sensitivity to fungicide. When the isolates were tested on the Chinese differentials of 19 wheat cultivars, 72 races were identified, which belonged to three groups, including the Guinong 22 group (48.45%), Hybrid 46 group (31.62%), and Suwon 11 group (19.93%). The three most predominant races were CYR34 (15.46%), G22-14 (11.68%), and CYR32 (10.65%). When the isolates were tested on the 18 Yr single-gene differentials, 95 races were identified, but none of the isolates were virulent to either Yr5 or Yr15. Cluster analyses of the virulence data based on the two sets of differentials and the SNP marker data consistently separated the Shaanxi Pst population into two clusters in the central part and southern part of the Province. Triadimefon sensitivity testing across different concentrations showed a broad range of half-maximal effective concentration (EC50) values, from 0.03 to 5.99 μg mL-1, with a mean EC50 of 0.46 μg mL-1. The majority of isolates (90.72%) were sensitive to the fungicide. The correlation analyses of the virulence, SNP marker, and the triadimefon sensitivity data showed no significant correlations, except a logarithmic relationship between the EC50 value and the number of avirulence factors. This study is the first to determine the relationship of virulence and SNP markers with triadimefon sensitivity in a regional Pst population.The findings provide valuable insights for breeding resistant wheat cultivars and integrated management of stripe rust